2022
DOI: 10.1097/mlr.0000000000001729
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Method Evaluation of Louisiana’s Prerelease Medicaid Enrollment Program, 2017–2019

Abstract: Background: Over 600,000 people leave US prisons annually. Many are eligible for Medicaid upon release but may need support to enroll. Carceral facilities in nearly half of states have implemented systems to facilitate Medicaid access for those leaving incarceration, but there is limited information on program implementation models or outcomes. Objectives: To evaluate implementation and initial outcomes of Louisiana's prison-based Prerelease Medicaid Enrollment Program. Methods: In this mixed-methods study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We conducted a retrospective cohort study of Louisiana Medicaid claims data crosslinked with Louisiana Department of Public Safety and Corrections data. To create the dataset, all available Louisiana Medicaid claims data were matched with all available Louisiana Department of Public Safety and Corrections data by social security number, as in a previous analysis [ 24 ]. Data were fully anonymized prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a retrospective cohort study of Louisiana Medicaid claims data crosslinked with Louisiana Department of Public Safety and Corrections data. To create the dataset, all available Louisiana Medicaid claims data were matched with all available Louisiana Department of Public Safety and Corrections data by social security number, as in a previous analysis [ 24 ]. Data were fully anonymized prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A recent evaluation of the Program found that it was initially successful in increasing Medicaid enrollment [ 24 ]. While gaining access to health coverage after contact with the criminal legal system may not be sufficient to ensure use of some health services [ 25 ], there is some evidence that Medicaid coverage upon release facilitates use of health care [ 24 , 26 ], including among people with a history of substance use [ 27 ] or serious mental illness [ 28 ]. With limited exception [ 29 ], there is a paucity of information about whether the timing of enrollment (i.e.…”
Section: Introductionmentioning
confidence: 99%